Associations between dietary diversity and micronutrient status of children aged 6–23 months in rural Burkina Faso and Kenya: cross-sectional findings from the ALIMUS study - Adi Lukas Kurniawan; Anais Gonnet; Grace Wothaya Kihagi; Erick Agure; Raissa Sorgho; Fanta Zerbo; Ali Sié; Erick M. O. Muok; Ina Danquah (BMJ Nutrition, Prevention & Health, 2026)
Objective This study examined the associations between dietary diversity, food variety and micronutrient status among young children in rural Burkina Faso and Kenya. Methods Cross-sectional baseline data from 1307 children aged 6–23 months from a cluster-randomised controlled trial, the ALIMUS–“We are feeding” study, were analysed. The Dietary Diversity Score (DDS), Minimum Dietary Diversity (MDD) and Food Variety Score (FVS) were assessed using a food propensity questionnaire. Nutrient adequacy ratios for iron, zinc, selenium and vitamin A, and the mean adequacy ratio (MAR) were calculated. We calculated prevalence ratios (PRs) with 95% CIs for the associations between dietary indicators and micronutrient adequacy using a modified Poisson regression model. Receiver operating characteristic analysis was used to determine optimal cut-offs for DDS and FVS to predict MAR. Results 89% of the children (median age: 16 months, IQR: 11, 20; boys: 51.6%) met MDD, with a higher prevalence in Kenya (95.1%, 95% CI 93.2% to 96.5%) than in Burkina Faso (82.8%, 95% CI 79.7% to 85.6%). Higher DDS and FVS were associated with living in smaller households, higher levels of maternal education and maternal employment. Children who met MDD had a significantly higher prevalence of adequate intakes of iron (PR=16.0), vitamin A (PR=3.5), zinc (PR=1.7) and selenium (PR=1.2). DDS ≥6.5 and FVS ≥20.5 were optimal cut-offs for predicting MAR (area under the curve: 0.89 and 0.91, p